(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article explores the challenges and opportunities surrounding the financing of innovative scientific research. Through an analysis of funding trends, institutional factors, and policy considerations, it highlights key issues impacting the ability to advance groundbreaking discoveries. The article reviews relevant literature, presents data on R&D investment patterns, and discusses the complex dynamics influencing research funding. It concludes with recommendations for optimizing financing mechanisms to drive innovation while balancing societal priorities.